Factores sociodemográficos y culturales que influyen en la donación y trasplante de órganos en los habitantes de Zamora - Iñahuazo Chalán, Jessica Isabel (2022)
This research refers to the topic of organ donation and transplants, especially in developing countries, as is the case of Ecuador, a country where the single national waiting list significantly exceeds the tissues and organs that can be transplanted. The investigation of the present problem was carried out with the interest of knowing what are the sociodemographic and cultural factors that influence donation and transplantation of organs and systems. The general objective of the present research will be “to determine the sociodemographic and cultural factors that influence in organ donation and transplantation in the inhabitants of Zamora”. The objectives seek to: analyze the relationship between sociodemographic factors and attitude on organ donation and transplantation in the inhabitants of Zamora, to compare the relationship between cultural factors and attitudes towards organ donation and transplantation in the inhabitants of Zamora and identify the level of knowledge about the donation and organ transplantation in the inhabitants of Zamora. This study will have a qualitative focus, it will be descriptive and transversal, Inhabitants of the Zamora canton, of the province from Zamora Chinchipe. The present study concluded that among the sociodemographic factors only the marital status has a significant relationship towards the negative attitude towards the transplantation and organ donation, it also does not show a relationship between religion and a negative attitude towards transplantation and organ donation, however, ignorance on the subject significantly influences the negative attitude towards donation and organ transplant